Digital participation of brain tumour patients in the assessment and treatment of communication disorders - Weiss Lucas, Carolin; Kochs, Sophia; Jost, Johanna; Loução, Ricardo; Kocher, Martin; Goldbrunner, Roland; Wiewrodt, Dorothee; Jonas, Kristina (Frontiers in Psychology, 2024)
Communication deficits have a severe impact on our social interactions and health-related quality of life. Subtle communication deficits are frequently overlooked or neglected in brain tumour patients, due to insufficient diagnostics. Here, digital tools may represent a valuable adjunct to the conventional assessment or therapy setting but might not be readily suitable for every patient. This article summarises results of three surveys on the readiness for telemedicine among high-grade glioma patients (a) versus matched healthy controls (b), as well as on the speech and language therapists' view on the use of digital tools for the diagnosis and therapy of neurogenic communication disorders in-and outside neuro-oncology (c).73 surveyed controls were instructed to imagine themselves with a severe disease and were propensity-score matched to 56 interviewed high-grade glioma patients (age median: 59 years; 48% males). Moreover, 23 speech and language therapists participated (61% <35 years; all females). The respective surveys assessed (a,b) the motivation for participation in telemedical assessments and supposed influencing factors, and (c) the use potential of digital assessment and therapy technologies in daily routine, with a spotlight on brain tumour patients and the future prospects of respective telemedical interventions.The vast majority of the interviewed high-grade glioma patients was open to digitisation, overall well-equipped and felt sufficiently skilled, whereas only few respondents (15%) refused such receptiveness. The factorial analysis showed that digital offers would be of particular interest for patients in reduced general health condition (p=0.03) and those who live far from specialised treatment services (p=0.03). The particular motivation of these subgroups seemed to outweigh the effects of age, equipment and internet skills, which were only significant in the control cohort. The therapists' survey demonstrated a broad consensus on the need for improving the therapy access of brain tumour patients (64%) and strengthening their respective digital participation (78%), although digitisation seems to have yet hardly entered the therapists' daily practice.In summary, the combined results of the surveys call for a joint effort to enhance the prerequisites for digital participation of patients with neurogenic communication disorders, particularly in the context of heavily burdened high-grade glioma patients with limited mobility.